There's an app for that: Teaching entomology in the online age. Issue 2 (18th July 2022) - Mech, Angela; Rosenberger, Derek; Fanning, Philip; Riggins, John J.; Aukema, Brian; Hartshorn, Jess
Abstract: Effective educational tools are needed to facilitate learning of organismal and ecological sciences in the virtual setting. For entomology laboratory classes, physically collecting insects and curating them in formal collections encompass the traditional learning and assessment tools to introduce students to the natural world and increase their curiosity and interest in insects. Virtual learning, however, creates issues with this modality. Using pre‐ and post‐surveys across five universities based on a new lab activity, we sought to determine whether using a digital platform named iNaturalist stimulated observation, curiosity, and interest in insects. iNaturalist positively affected each measure, most strikingly among biology and zoology majors who increased observation by 15%, curiosity in identification by 39%, and interest by 16%. Increases in observation and curiosity in insects were positively correlated with increases in interest in entomology as a whole. Our findings suggest that virtual tools such as iNaturalist may promote positive course outcomes. Core Ideas: Students were assigned a collection using iNaturalist in entomology courses. iNaturalist had a positive effect on observation, curiosity, and interest in insects. iNaturalist was an engaging tool that had positive learning outcomes for students.